Penggunaan Empat Set Primer dalam Mendeteksi Tryapanosoma evansi pada Mencit dengan Teknik Polymerase Chain Reaction (PCR) - Dias Aprita Dewi; Fitrine Ekawasti; April H. Wardhana; Dyah H. Sawitri (Jurnal Sains dan Teknologi Peternakan, 2019)
Diagnose technique for detection Tryapanosoma evansi have been developed for many years, including Polymerase Chain Reaction (PCR). One of fundamental factors on this technique is primer desain which possess high sensitivity and specificity. The aim of the current study was to examine four primer sets for detection of T. evansi on mice. They were ITS 1, ESAG 6/7, RoTat 1.2 VSG, TBR1/2 and TR3/TR4. Balitvet Culture Collection (BCC) – Bangkalan isolate of T. evansi was was injected into two male mice DDY strain. Three days after infection, blood mice was collected and stored at -20oC. In addition, some blood was dropped on the filter paper and kept at 4oC. Another mice was killed and some tissues (brain, liver, lung, heart, spleen and kidney) were removed from mice and preserved into 80% Ethanol and then they were stored -20oC. All samples were amplified using five primer sets and repeated twice. The results demonstrated that all primers (ITS 1, ESAG 6/7, RoTat 1.2 VSG, TBR1/2 and TR3/TR4) were able to detect T. evansi on all samples (the blood, the filter paper and all tissues). In order to detect T. evansi in the field, primer ITS-1 is recommended because it is able to discriminate some spesies T. evansi in livestock and generate a good intensity of DNA band from tested samples.